Protecting Disadvantaged Victims of Crime in Vietnamese Law - Ha, Nguyen Van (VNU Journal of Science: Legal Studies; Vol 41 No 3DO - 10.25073/2588-1167/vnuls.4692, 2025)
Vietnamese law has established specific, detailed regulations that are periodically adjusted, amended, supplemented, and replaced to align with socio-economic conditions in order to protect crime victims. This approach not only focuses on punishing and prosecuting offenders to maintain legal order and uphold the rigor and fairness of the law, but it also gradually incorporates comprehensive regulations aimed at protecting victims throughout the process - from the initial infringement to the point where they can independently exercise their rights as they did prior to the violation. Victims of crime are central subjects defined and protected by law, with the purpose of minimizing and preventing harm caused by criminal acts. This article discussses the protection of crime victims, particularly those from vulnerable groups under current Vietnamese law, with a focus on children, persons with disabilities, and the elderly. It further aims to identify areas requiring further research and improvement in this new context.